The Use of Code-Switching and Code-Mixing in English Teaching-Learning Process - Rika Novianti; Mashadi Said (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2021)
The research aims to find out types of code-switching and code-mixing, the functions of code-switching and code-mixing in the English teaching-learning process. The method of this research is a qualitative descriptive method. The data source is English teachers’ utterances in teaching English as a foreign language, the teacher’s language of instructions. The results of the research are: 1) the students and teachers used code-switching and code-mixing in the process of communication in the classroom; 2) in code-switching, they used inter- sentential, intra- sentential, and tag switching; 3) in code-mixing, they used alternation and insertion; 4) the functions of code-switching include reiteration, message qualification, personalization, referential, and poetic; 5) the function of code-mixing is to draw students’ attention in learning. The findings imply that code-switching and code-mixing are necessary to facilitate learning.